TINDAK TUTUR DIREKTIF DI MADRASAH ALIYAH NEGERI SAMPIT (DIRECTIVES SPEECH ACTS IN MADRASAH ALIYAH SAMPIT) - Dina Yaumil Amal (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2022)
AbstractDirectives Speech Acts in Madrasah Aliyah Sampit. This study describes the form of directive speechacts, and the function of directive speech acts in the interaction between teachers and students inMadrasah Aliyah Negeri Sampit. The approach in this study uses a qualitative approach. The data inthis study were in the form of speech data in teacher and student interactions obtained fromobservations, field notes, recording and interviews. The data analysis is carried out through threestages, namely (1) data reduction, (2) data presentation, and (3) inference / verification. From thethree data the final conclusions are obtained by triangulation and checking. Based on the results ofthe study, found the directive speech acts found by researchers in the form of imperative form,introgative form, declarative form and directive speech act function in the Sampit state madrasaenvironment found by researchers, First, directive speech acts to save face in every social interaction,people people behave so that their facial desires are respected. Second, directive speech acts to avoidconflict. Third, directive speech acts for acts of respect.Key words: pragmatic, speech act, teacher and student, form, function, directive speech actsAbstrakTindak Tutur Direktif di Madrasah Aliyah Negeri Sampit. Penelitian ini mendeskripsikan wujudtindak tutur direktif, dan fungsi tindak tutur direktif dalam interaksi antara guru dan siswa di MadrasahAliyah Negeri Sampit. Pendekatan dalam penelitian ini menggunakan pendekatan kualitatif. Datadalam penelitian ini berupa data tuturan interaksi guru dan siswa diperoleh dari observasi, catatanlapangan, perekaman dan wawancara. Pada analisis data dilakukan melalui tiga tahap, yaitu (1)reduksi data, (2) penyajian data, dan (3) penyimpulan/verifikasi. Dari ketiga data diperoleh kesimpulanakhir dengan triangulasi dan pengecekan. Berdasarkan hasil penelitian, ditemukan wujud tindak tuturdirektif yang ditemukan peneliti berupa wujud imperatif, wujud introgatif, wujud deklaratif dan fungsitindak tutur direktif di lingkungan Madrasah Negeri Sampit yang ditemukan peneliti, Pertama, tindaktutur direktif untuk menyelamatkan muka pada setiap interaksi sosial, orang-orang berprilaku agarkeinginan muka (face) mereka dihormati. Kedua, tindak tutur direktif untuk tindakan menghindarikonflik. Ketiga, tindak tutur direktif untuk tindakan menghormati.Kata-kata kunci: Pragmatik, tindak tutur, guru dan siswa, bentuk direktif, fungsi direktif